Construction Quality and the Economy A Study at the Firm Level - Sui Pheng, Low.; Shing Hou, Lau.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the relationship between construction quality and the state of the Singapore national economy, and describes how construction quality is affected as contracting firms strategically manage issues relating to profitability and survivability during economic boom and bust cycles. Adopting a three-pronged approach to explain the key issues, the book first explains the effect of the state of the Singapore national economy (boom or bust) on the construction quality delivered by contracting firms. Secondly, it explains how contracting firms respond to the performance of the national economy through their dynamic bidding strategies, leading to significant quality trade-offs in some instances, especially when there is imprecise market information. Thirdly, it recommends various strategic measures that key stakeholders and government policy-makers can take to circumvent the quality trade-off in the construction industry when faced with dynamic fluctuations in the performance of the national economy. Although the book focuses on Singapore, it appeals to a global audience since countries worldwide (and their respective building-related stakeholders) face the same issues in terms of the time-cost-quality trade-off decision-making process involving the entire supply chain.
Introduction -- The Economy and the Construction Industry -- Government's Role in a High Quality Built Environment -- Firm Characteristics and Strategies -- Firm's Trade-Off Decisions and Theory of Firm Behavior -- The Conceptual Framework -- Research Design and Methodology -- Survey Results Analysis and Discussion -- Case Study Results Analysis and Discussion -- Experts Interviews on Triangulated and Non-Triangulated Findings -- Conclusions. .
Keywords: Construction industry -- Management; Project management; Industrial Management; Construction Management; Project Management; Industrial Management